Recovery of Mediterranean Vegetation after Recurrent Forest Fires: Insight from the 2010 Forest Fire on Mount Carmel, Israel. (1st September 2015) - Tessler, Naama; Sapir, Yuval; Wittenberg, Lea; Greenbaum, Noam
Abstract: The December 2010 forest fire on Mount Carmel – the largest recorded in Israel – burned about 2500 ha of Mediterranean forest. We documented the immediate and short‐term changes of the vegetation following this fire. Relative vegetation cover and plant species richness were sampled in five sites in spring 2009 and 2010, prior to the fire, and were re‐sampled in 2011 and 2012. The number of recurrent fires (between 0 and 3) and time intervals between fires were documented for each site. We observed a strong decrease in total vegetation cover, associated with reduction of relative cover of woody vegetation. In the second year after the fire, shrubs and dwarf shrubs became dominant at all sites. Time intervals between fires played an important role in determining the extent of regeneration of the vegetation cover and plant species richness. Plant species richness immediately decreased after the fire in sites with a short fire interval, while in sites with a long fire interval, plant species richness increased. Relative plant cover was associated with the time from the last previous fire, and this association differed among different plant groups. These results suggest that vegetation and plant community regeneration after recurrent fires is accelerated when time intervals between fires are longer, whereas high fire frequency may suppress vegetation regeneration. Based on the results, we propose that forest regeneration after recurrent fires depends largely on time from the previous fire, rather than on the number of previous fires. Copyright © 2015 John Wiley & Sons, Ltd.